The Effects of Perceived Service Quality, Perceived Safety towards Satisfaction, Loyalty and Complaints among Urban Rail Passengers - Hamid, Nora; Nurul Izzati Baharudin, (Research in Management of Technology and Business, 2023)
Rail transportation user growth has been growing rapidly every year, particularly in urban cities. As the population grows, the total number of accidents and incidents that involve urban rail services also will be increasing too. Therefore, it is also will affect service quality of urban rail. The aim of this study is to identify perception from the LRT Kelana Jaya line passengers except Malaysian disabled person designation (OKU) passengers in terms of a few factors such as perceived safety, perceived service quality, passengers’ satisfaction, complaints and loyalty. Besides, descriptive analysis and Spearman correlation coefficient used as a tool to analyze the research data. There are five hypotheses discussed in this study. The results shows that service quality and safety has a significant relationship between customer satisfactions and customer satisfaction towards customer loyalty. A total of 263 valid data has been collected through the distribution of online and offline form. Other than that, the findings of this study cannot be applied to LRT Kelana Jaya line users as it only covers a very small part of the population, and the researcher cannot generalize the result as a whole. Thus, it was suggested for future studies to make an interview or observations towards the passengers to know their perception and behavior. The result of this study gives benefit to the rail operator to improvise on how they improve customer complaints. This is because, if the company can handle customer complaint nicely, they can increase their customer satisfaction and loyalty indirectly.